Population and genomic analysis of the genus Halorubrum - Fullmer, Matthew S.; Soucy, Shannon M.; Swithers, Kristen S.; Makkay, Andrea M.; Wheeler, Ryan; Ventosa, Antonio; Gogarten, J. Peter; Papke, R. Thane (Frontiers in Microbiology, 2014)
The Halobacteria are known to engage in frequent gene transfer and homologous recombination. In order for stably diverged lineages to be maintained there must be some checks on the rate of recombination between them. We surveyed a group of isolates from the Aran-Bidgol endorheic lake in Iran and sequenced a selection of them. Multi-locus sequence analysis and Average Nucleotide Identity revealed multiple clusters (phylogroups) of organisms present in the lake. While two of these clusters displayed numerous signs of sharing an exchange bias towards others in their group while showing reduced rates of exchange with other clusters. However, a third cluster, composed in part of named species from other areas of central Asia, displayed many indications of not having a unified set of exchange partners. We conclude that barriers to efficient gene exchange exist between the two purely Aran-Bidgol phylogroups and that the cluster with members from other regions is not a single population and likely reflects an amalgamation of several populations.